Strategi Guru Akidah Akhlak dalam Membina Kesantunan Siswa Kelas VII di MTs Al-Washliyah Stabat - Ahmad Khairuddin (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the strategies employed by Aqidah Akhlak teachers in fostering politeness among seventh-grade students at MTs Al-Washliyah Stabat, as well as to identify the supporting and inhibiting factors influencing the process. This research employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving Aqidah Akhlak teachers, the head of the madrasa, subject teachers, and students. The data were analyzed using the Miles and Huberman interactive analysis model, while data validity was ensured through source triangulation and technique triangulation. The findings revealed that Aqidah Akhlak teachers implemented several strategies in fostering students’ politeness, including exemplary behavior, habituation, advice, discussion methods, and the integration of moral values into the learning process. These strategies contributed positively to students’ polite behavior, such as greeting teachers respectfully, using polite language, and showing respect toward teachers and peers. Supporting factors included a religious school environment, teacher role models, and character-building programs within the madrasa. Meanwhile, inhibiting factors included students’ diverse backgrounds, limited self-awareness, family environment, peer influence, and social media exposure. Therefore, collaboration among teachers, parents, and the school environment is essential in strengthening students’ politeness and character development.